Digital Technography: A Methodology for Interrogating Emerging Digital Technologies and Their Futures. (September 2022) - Berg, Martin
This article introduces "digital technography" as a methodology to interrogate and voice emerging digital technologies and their anticipated futures. I demonstrate, with reference to recent research on wearable self-tracking devices, digital food technologies, and platforms for work automation, how one can gain an understanding of these technologies by attending to the materials in which they are promoted; and actively engaging with them imaginatively and self-reflexively as a social scientist. This article outlines a digital technographic methodology centered around the three conceptual anchors of specification, valorization, and anticipation, all of which pertain to how a digital technology aims and perhaps even aspires to become a part of everyday life.